2023
DOI: 10.1371/journal.pgph.0001782
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections amongst men who have sex with men (MSM) in South Africa

Abstract: There is limited data about bacterial STIs in MSM populations in sub-Saharan Africa. Our retrospective analysis used data from the HVTN 702 HIV vaccine clinical trial (October 2016 to July 2021). We evaluated multiple variables. Polymerase chain reaction testing was conducted on urine and rectal samples to detect Neisseria gonorrhoea (NG) and Chlamydia trachomatis (CT) every 6 months. Syphilis serology was conducted at month 0 and thereafter every 12 months. We calculated STI prevalence and the associated 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…This was highlighted in the first systematic review and meta-analysis of global syphilis prevalence in this key population, in which sub-Saharan Africa contributed only 7% of the data points during the 20-year survey period. 35s A limited number of South African studies have conducted syphilis testing among MSM, with results revealing seroprevalences ranging from 5.2%, 14 11% (MSM), 8 and 12.5% (MSM and transgender women) 6 to 21.6% (MSM) 3 . The latter findings are in keeping with the RPR seropositivity observed in our cohort.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This was highlighted in the first systematic review and meta-analysis of global syphilis prevalence in this key population, in which sub-Saharan Africa contributed only 7% of the data points during the 20-year survey period. 35s A limited number of South African studies have conducted syphilis testing among MSM, with results revealing seroprevalences ranging from 5.2%, 14 11% (MSM), 8 and 12.5% (MSM and transgender women) 6 to 21.6% (MSM) 3 . The latter findings are in keeping with the RPR seropositivity observed in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…The high rates of asymptomatic rectal STIs we observed mirror rectal gonorrhea and/or chlamydia prevalence rates detected by others 3,6 . In contrast to other studies in our country, CT was not the predominant rectal pathogen 14 . Studies have demonstrated low LGV positivity rates (<5%) among MSM positive for rectal CT infection, 22–24 and hence, our small sample size may have contributed to the failure to detect this bacterial pathogen.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Additionally, the studies reveal that the bacterial STI burden is greater in MSM compared to non-MSM males, emphasizing the need for tailored healthcare services for MSM. STI prevalence among MSM also seem to remain relatively stable over time [67]. Men who have sex with men (MSM) and participate in unprotected anal intercourse with casual partners face a significant risk of contracting sexually transmitted infections (STIs).…”
Section: Level Of General Knowledgementioning
confidence: 99%